Chemical free synthesis of graphene oxide in the preparation of reduced graphene oxide-zinc oxide nanocomposite with improved photocatalytic properties - Meti S.; Rahman M.R.; Ahmad M.I.; Bhat K.U. (My University, 2025)
In the present investigation, the reduced graphene oxide – zinc oxide (rGO-ZnO) was prepared by rapid microwave-assisted hydrothermal technique. The chemical free graphene oxide (GO), synthesized by Tang Lau technique, was used in the preparation of rGO-ZnO nanocomposite. The GO gets reduced to rGO during microwave irradiation and provides the necessary nucleation site for the ZnO nanorods to grow in [0 0 0 1] direction. These ZnO nanorods were completely wrapped with rGO sheets, confirmed by the synchrotron XRD and TEM techniques. The phases and cell parameters were calculated by Rietveld method. The prepared composite was used for the photodegradation of methyl orange (MO) dye from water under UV light. Investigation revealed that the incorporation of rGO into the ZnO increased the photodegradation ability of the bare ZnO. The performance of the composite is also compared with the rGO-ZnO nanocomposite, where rGO was prepared by Hummer's method. rGO obtained from Tang Lau method formed stable and efficient composite with ZnO and exhibited higher activity compared to the composite, wherein rGO was prepared from conventional Hummer's method. Under UV light, the ZnO liberates photoelectrons which reacts with surface oxygen to form superoxide radicals (O − 2 ) and (OH − ) in the water medium. The rGO nanosheets could reduce the charge recombination during the reaction. The active species adsorbs the MO molecules and degrades into CO 2 , H 2 O and other byproducts. More than 3.5 times increase in the rate constant was observed for rGO-ZnO compared to the bare ZnO. © 2018 Elsevier B.V.